Immunomodulatory effects of alpha vs beta radiopharmaceutical therapy in murine prostate cancer - Ferreira, Carolina A.; Potluri, Hemanth K.; Mahmoudian, Mojdeh; Massey, Christopher F.; Grudzinski, Joseph J.; Carston, Amanda M.; Clemons, Nathan B.; Idrissou, Malick Bio; Thickens, Anna S.; Rosenkrans, Zachary T.; Choi, Cynthia; Kerr, Caroline P.; et al. (Frontiers in Immunology, 2025)
BackgroundRadiation therapy can modulate the tumor microenvironment (TME), influencing antitumor immune responses. This study compared the immunomodulatory effects of alpha-emitting (225Ac) and beta-emitting (177Lu) radiopharmaceutical therapies (RPT) using NM600 in murine prostate cancer models.MethodsWe assessed immunological changes in TRAMP-C1 and Myc-CaP tumor models treated with 225Ac-NM600 or 177Lu-NM600. Flow cytometry was used to profile immune cell populations, activation markers, and checkpoint molecules, while multiplex assays analyzed cytokine and chemokine expression.ResultsIn general, 225Ac-NM600 elicited stronger immunomodulatory effects than 177Lu-NM600, including cell line dependent increased CD8/Treg ratios, activation of effector and memory T cells, and depletion of suppressive Tregs and MDSCs. The treatment elevated Th1 cytokines, pro-inflammatory chemokines, and checkpoint molecules like PD-1 on CD8+ T cells and PD-L1 on MDSCs, creating a more “hot” TME.ConclusionAlpha-emitting 225Ac-NM600 demonstrated superior ability to enhance antitumor immunity compared to beta-emitting 177Lu-NM600. These findings support the use of 225Ac-NM600 in combination with immunotherapies for advanced prostate cancer treatment.